The quest for an improved solid oxide fuel cell (SOFC) electrolyte: exploring bismuthate material - Kiefer, Mathias Ameer (My University, 2022)
In this project, several bismuthate (Bi2O3) materials were investigated as improved solid oxide fuel cell (SOFC) electrolytes with the overall aim of uncovering an electrolyte that is superior to the more popular zirconia (ZrO2) and ceria (CeO2) varieties. Investigating materials for application as SOFC electrolytes involves considering several criteria which were investigated throughout this thesis. The bismuthates investigated were synthesized using the citrate sol-gel method and the characterization techniques utilized were powder X-ray diffraction (PXRD) with Rietveld refinement, Raman spectroscopy and electrochemical impedance spectroscopy (EIS). An investigation of the structural stability, ionic conductivity and in situ δ-phase formation of yttrium doped bismuthates showed that the transition from a phase mixture to the δ-phase occurs at ~550-600 oC. For dopant concentrations less than 25%, the cubic phase was found to not be fully stabilized at room temperature. Additionally, the thermal expansion and ionic conductivity of the δ-phase was found to decrease with increasing dopant content. An investigation of the phase stability of yttrium-doped bismuthates, with emphasis placed on stability criteria which are often overlooked, showed that the cubic and tetragonal polymorphs are metastable under ambient conditions. Additionally, the spontaneous formation of both the rhombohedral and subcarbonate phases was evident. The spontaneous formation of bismuth subcarbonate occurs directly from the reaction of the stabilized bismuthates with atmospheric carbon dioxide and this phenomenon was reported for the first time in this work. Pelletization and additional sintering as well as annealing under an inert atmosphere was found to enhance the long term phase stability characteristics of the cubic phase. Additionally, non-linear thermal expansion behaviour was observed for 27.5% dopant content and for 15% dopant content, and an abrupt increase in cubic phase unit cell volume was observed which indicates the presence of an unidentified phase change during the thermal cycle. An investigation of the thermal expansion behaviour of yttrium-doped bismuthates using in situ total scattering studies revealed that non-linear thermal expansion behaviour observed for 27.5% yttrium content was linked to changes in the state of disorder of the cation sublattice. For 10% yttrium content and for 10% yttrium, 1% aluminium content, abrupt changes in cubic phase unit cell volume were found to be due to the tetragonal-cubic phase transformation and a mechanism for this was proposed. Changes in the cubic phase coefficient of thermal expansion (CTE) during the thermal cycle were also observed for all dopant content levels and these changes were found to be linked to changes in the state of disorder of the cationic sublattice. IV The rhombohedral phase of bismuth oxide has recently emerged as a promising SOFC electrolyte material and the phase stability window of this phase was investigated using yttrium, lanthanum and aluminium doping regimes. It was established that the phase stability window is dependent on both the synthetic method and nature of the dopant species utilized. The thermal stability and phase behaviour of the rhombohedral phase, which has been sparsely reported, was investigated in situ over 360-656-360 oC. Complex phase transformation characteristics were evident during the thermal cycle along with abrupt changes in the thermal expansion of both the cubic and rhombohedral phases. These changes were found to be indicative of the rhombohedral-cubic phase transformation and the separation of the (009) and (104) peaks of the rhombohedral phase were identified as an excellent visual marker for this transformation.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Science, School of Chemistry, University of the Witwatersrand, Johannesburg, 2022